The Importance of Human Rights - Andersson, Henrik (De Ethica, 2024)
This paper argues that recent advancements in value theory can inform discussions on the interrelation of human rights. More precisely it is argued that the importance of human rights, i.e., the ranking of their priority, cannot be fully accounted for by "more important" and "equally as important". The concept of "on a par importance" is introduced and it is argued that this concept captures implicitly held intuitions in the debate. Furthermore, with this new conceptual insight, it is possible to justify certain assumptions that previously lacked a justificatory ground.